A review on frequency support provision by wind power plants: Current and future challenges. (January 2018) - Attya, A.B.; Dominguez-Garcia, J.L.; Anaya-Lara, O.
Abstract: The continuing increase of wind energy penetration into power systems, in combination with the retirement of conventional generation, raises new challenges for the maintenance of power system stability. This paper presents a comprehensive review of wind power plant capabilities to provide frequency support and the corresponding methods available in the published literature are thoroughly analysed and compared. The topic is covered from different perspectives giving a comprehensive overview on the work carried out in this field. In addition, the integration of energy storage technologies and dispatching of wind farms during frequency deviations are thoroughly discussed. Finally, technical challenges, future research lines and general recommendations are provided.